Financial wellness programs in the workplace: Employer motivations and experiences. (2nd October 2019) - Frank-Miller, Ellen G.; Despard, Mathieu; Grinstein-Weiss, Michal; Covington, Meredith
Abstract: Employee financial wellness programs (EFWPs) are a benefit innovation that promise to address the financial challenges of employees while also benefiting employers. Results from a mixed-methods study of employers suggest early adopters appear to be motivated primarily by a desire to help employees. EFWP success may depend on promotion by organizational champions. Programs that accommodate confidentiality needs appear more likely to succeed. Research is needed to determine whether EFWPs improve financial outcomes and work performance of employees. However, employee financial well-being may be affected by poor compensation and work conditions that erode the value of EFWPs to lower-wage employees.